Effects of early mobilization on patients in the intensive care unit: An integrative review - Márcio Cavalcante Marcelino; Djavan Gomes Leite; Weslley Barbosa Sales; Giovanna Pontes Vidal (Open Journal of Pain Medicine - Peertechz Publications, 2023)
Introduction: The deleterious effects of immobility in the ICU can be minimized by having early mobilization within their strategies, which consists of an interprofessional plan that proposes the improvement of inactivity and which aims to reduce the problems caused by hospitalization with appropriate exercises for high-age individuals. Risk and its bed.  Objective: To identify the effects of this physical therapy technique on patients hospitalized in this hospital sector.  Methodology: This is an integrative review, with a survey in March 2020, in the Scientific Electronic Library Online (SCIELO), PubMed and Virtual Health Library (VHL) databases, with the inclusion criteria: experimental articles and clinical cases with purposes included in the study strategy, written in Portuguese and English, published between 2015 and 2020, available in full in the online collection and exclusion: articles referring to another area of ​​health, incomplete and integrative, systematic reviews, bibliographic or meta-analysis, using the descriptors: "Efficacy", "Early Mobilization" and "UCI".  Results: The findings from this research made it possible to identify that physiotherapy is effective in carrying out early mobilization protocols, providing important results, such as: length of stay, important gains in functionality, pain reduction, improvement in respiratory muscles and time reduction of mechanical ventilation.  Conclusion: Physiotherapy is important in the process of hospitalization of ICU patients, especially in the use of early mobilization protocols, and these were effective in the studies selected for this research.